2016
DOI: 10.1038/ncomms10549
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodeller SMARCA4 recruits topoisomerase 1 and suppresses transcription-associated genomic instability

Abstract: Topoisomerase 1, an enzyme that relieves superhelical tension, is implicated in transcription-associated mutagenesis and genome instability-associated with neurodegenerative diseases as well as activation-induced cytidine deaminase. From proteomic analysis of TOP1-associated proteins, we identify SMARCA4, an ATP-dependent chromatin remodeller; FACT, a histone chaperone; and H3K4me3, a transcriptionally active chromatin marker. Here we show that SMARCA4 knockdown in a B-cell line decreases TOP1 recruitment to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 69 publications
(117 reference statements)
0
64
0
3
Order By: Relevance
“…The topoisomerases TOP1 and TOP2 cooperate to optimize transcription through induction of single-strand breaks and double-strand breaks, respectively (Pommier et al, 2016;Teves and Henikoff, 2014;King et al, 2013;Husain et al, 2016). Several reports have shown that TOP2 isoforms are associated with DSBs and transcriptional activity (Ju et al, 2006;Madabhushi et al, 2015;Bunch et al, 2015;Canela et al, 2019).…”
Section: Top1 Is Involved In Rad51-associated Dsbsmentioning
confidence: 99%
“…The topoisomerases TOP1 and TOP2 cooperate to optimize transcription through induction of single-strand breaks and double-strand breaks, respectively (Pommier et al, 2016;Teves and Henikoff, 2014;King et al, 2013;Husain et al, 2016). Several reports have shown that TOP2 isoforms are associated with DSBs and transcriptional activity (Ju et al, 2006;Madabhushi et al, 2015;Bunch et al, 2015;Canela et al, 2019).…”
Section: Top1 Is Involved In Rad51-associated Dsbsmentioning
confidence: 99%
“…Importantly, the DNA relaxation activity of Top1 in human cell lines is stimulated by interaction with the phosphorylated C-terminal domain of RNAPII and that this association facilitates promoter escape as well as elongation past natural pause sites. In addition to a direct interaction with RNAPII, human Top1 is recruited to transcriptionally active chromatin via interaction with chromatin remodeling factors [13]. …”
Section: Top1 As a Regulator Of Genome Stabilitymentioning
confidence: 99%
“…The significance of Top1 in suppressing the accumulation of R-loop and/or G4-DNA structures at the switch regions is expected to be relevant to the effectiveness of acquired immunity as well as the development of B cell-derived malignancies. Indeed, the IgH-cMYC translocation frequency, along with CSR efficiency, was recently shown to be significantly elevated by knock-down of Top1 or SMARCA4, a chromatin remodeler responsible for recruiting Top1 to IgH switch regions in an AID-expressing B-cell line [13]. Making an indisputable connection between Top1 regulation in cancer development and its role as a regulator of genome instability at G4 sequences will require further research.…”
Section: Top1 As a Regulator Of Genome Stabilitymentioning
confidence: 99%
“…Moreover, Exo1 extensively resects both telomere ends, generating transient long 3′ overhangs in S phase/G2 phase checkpoint. CST/AAF, a DNA polα primase accessory factor, binds POT1b and shortens the extended overhangs produced by Exo1, likely through fill‐in synthesis 20, 21. Furthermore, genetic variants in telomere maintenance genes are associated with genomic instability, cancer risk and cancer metastasis 22, 23, 24…”
Section: Introductionmentioning
confidence: 99%
“…CST/AAF, a DNA pola primase accessory factor, binds POT1b and shortens the extended overhangs produced by Exo1, likely through fill-in synthesis. 20,21 Furthermore, genetic variants in telomere maintenance genes are associated with genomic instability, cancer risk and cancer metastasis. [22][23][24] In this study, we attempted to elucidate TLR4 functions during the malignant growth of liver cancer stem cells.…”
mentioning
confidence: 99%